MOTIVATION AND TOURISTS’ LOYALTY IN PERFORMING ARTS FESTIVALS: THE MEDIATOR ROLE OF QUALITY AND SATISFACTION - Amorim, Daniela; Jiménez-Caballero, José Luís; Almeida, Paulo (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
Festival tourism has been growing considerably over the years, acquiring a prominent position and with strong popularity in society. Festivals and/or events promote a cultural exchange at international, national and local levels, with the opportunity for cultural sharing, from history and tradition, culinary and drinks, music and dance, involving all publics (organization, services, artists, participants and local inhabitants). Festivals are recognized as an effective strategy for host destinations promoting economic, social and cultural development. The present study aims to test the mediator role of quality and satisfaction in the relationship between the motivation in the choice of performing arts festivals and the loyalty of the tourists. The sample consisted of 532 respondents, collected at two performing arts festivals: Andanças festival (Portugal) and La Sierra festival (Spain). The results of the study show that tourists motivated to attend performing arts festivals, tend to perceive the festival as having quality, and are satisfied with the service, which in turn tend to revisit and recommend the festival. The study discusses the implications of the obtained results. It also presents limitations and suggests future studies.